Linking Demographic Profile to Family Influence and Career Decision Preferences - Faculin, Candy H.; Villares, Ofelia N.; Jortil, Mariza O. Jortil; Delantar, Alexander Franco A. (Transpublika Publisher, 2025)
Despite extensive literature on family and demographic factors influencing career choices, their specific intersection and impact on students in Business and Accountancy programs remain an underexplored area in the Philippines' higher education. This descriptive-correlational study investigated the impact of family and demographic factors on students' career choices at the College of Management, Business, and Accountancy at Cebu Institute of Technology–University (CIT-U). A total of 109 respondents, representing 10% of the enrolled population in the second semester of AY 2024–2025, participated in the survey. Descriptive statistics summarized students’ perceptions of family influence and career preferences, while Chi-square tests and logistic regression models assessed associations and predictive relationships. The results showed that while students increasingly value independence in their choices, families primarily influence career decisions through financial support and encouragement. Employability and financial feasibility emerged as the strongest drivers of career preferences, with financial uncertainty reducing career confidence. Demographic variables, such as age, gender, income, and parents’ education, showed significant associations with family influence or career preferences. However, older students demonstrated greater autonomy in decision-making. The study emphasized the importance of balancing family involvement, financial support, and career empowerment initiatives while respecting students’ independence. In line with the results, recommendations include strengthening family-inclusive career guidance, providing employability programs, and addressing financial challenges. Policymakers are recommended to promote equitable funding and access to higher education to support informed, independent decision-making for career choices.